Rdh54/Tid1 inhibits Rad51-Rad54-mediated D-loop formation and limits D-loop length - Shanaya Shital Shah; Stella Hartono; Aurèle Piazza; Vanessa Som; William Wright; Frédéric Chédin; Wolf-Dietrich Heyer (eLife, 2020)
Displacement loops (D-loops) are critical intermediates formed during homologous recombination. Rdh54 (a.k.a. Tid1), a Rad54 paralog in Saccharomyces cerevisiae, is well-known for its role with Dmc1 recombinase during meiotic recombination. Yet contrary to Dmc1, Rdh54/Tid1 is also present in somatic cells where its function is less understood. While Rdh54/Tid1 enhances the Rad51 DNA strand invasion activity in vitro, it is unclear how it interplays with Rad54. Here, we show that Rdh54/Tid1 inhibits D-loop formation by Rad51 and Rad54 in an ATPase-independent manner. Using a novel D-loop Mapping Assay, we further demonstrate that Rdh54/Tid1 uniquely restricts the length of Rad51-Rad54-mediated D-loops. The alterations in D-loop properties appear to be important for cell survival and mating-type switch in haploid yeast. We propose that Rdh54/Tid1 and Rad54 compete for potential binding sites within the Rad51 filament, where Rdh54/Tid1 acts as a physical roadblock to Rad54 translocation, limiting D-loop formation and D-loop length.